(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
This article examines research on the psychology of childbearing women and examines the emotional, cognitive, and behavioral patterns that characterize this demographic. This field examines how factors such as childbirth, child rearing, career choices, societal expectations, and personal identity shape women’s mental health and well-being during their reproductive years. Understanding these dynamics is critical to providing appropriate care and promoting holistic health in this population